A Model for Financial Programming - Mikkelsen, Jan (IMF Working Papers; Working Paper, 1998)
This paper presents a simple simulation model that enables the formulation of a consistent growth-oriented, medium-term adjustment program. The applied version is available in Excel (using data for El Salvador) and can be used directly as a financial programming tool that provides a range of standard IMF performance criteria together with a complete set of consistent accounts for the real, monetary, public, and external sectors of the economy. Medium- and long-term growth considerations are incorporated through a neoclassical production function at the same time as monetary and fiscal policies are adjusted to satisfy the requirements for internal and external balance.